2004
DOI: 10.1007/s10674-004-1025-8
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Phonological Awareness Throughout The School Years: The Case of a Transparent Orthography

Abstract: This article discusses phonological awareness, reading decoding and spelling of 280 Greek elementary school students of all grades, with and without reading difficulties. Phonological awareness was assessed by using ten oral activities. Decoding was assessed for accuracy and fluency by using 80 real words and 20 non-words. Spelling was also assessed by using two different scoring methods. We explored differences in performance and developmental images between children with and without reading difficulties. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(30 reference statements)
0
2
0
2
Order By: Relevance
“…Additionally, they reported that PA was a more powerful predictor of spelling than reading skill, and this was justified because spelling is heavily dependent on an explicit translation of phonemes into graphemes (Nikolopoulos et al, 2006). A strong relationship between PA and reading and spelling was also reported by Kotoulas (2004) who conducted a study with 280 Greek-speaking pupils with and without learning difficulties attending Grade 1 to 6 and also in a more recent study with Greek children by Kargiotidis et al (2021).…”
Section: Phonological Abilitymentioning
confidence: 91%
See 1 more Smart Citation
“…Additionally, they reported that PA was a more powerful predictor of spelling than reading skill, and this was justified because spelling is heavily dependent on an explicit translation of phonemes into graphemes (Nikolopoulos et al, 2006). A strong relationship between PA and reading and spelling was also reported by Kotoulas (2004) who conducted a study with 280 Greek-speaking pupils with and without learning difficulties attending Grade 1 to 6 and also in a more recent study with Greek children by Kargiotidis et al (2021).…”
Section: Phonological Abilitymentioning
confidence: 91%
“…Yet, spelling is more taxing than reading in Greek, as in other languages, as there are usually more ways to spell a phoneme than to read a grapheme (Kessler & Treiman, 2001). All phonemes are orthographically represented, although ambiguities and inconsistencies exist (Nunes et al, 2006) which can be overcome by knowing the spelling rules (Kotoulas, 2004). For example, some of the vowels can be spelled in multiple ways (e.g., /o/ can be spelled with <o> or <ω>; /e/ can be spelled with <ε> or <αι >; /i/ can be spelled with <ι, η, υ, οι, ει, υι>) (Kuperman et al, 2021).…”
Section: Spellingmentioning
confidence: 99%
“…Sesbilgisel farkındalığın gelişimi için bir evrensellik söz konusu olsa da sesbilgisel farkındalık, konuşulan dilin ortografik ve dilbilimsel yapısından etkilenir (Anthony ve Francis, 2005;Anthony, Williams, Duran ve Gillam, 2011;Ziegler ve Goswami, 2005). Örneğin alan yazında Türkçe, İtalyanca veya Yunanca konuşan çocukların İngilizce veya Fransızca konuşan çocuklara kıyasla hece ve sesbirim farkındalığını daha erken edindiklerine dair bulgular mevcuttur (Cossu, Shankweiler, Liberman, Katz ve Tola, 1988;Durgunoğlu ve Öney, 1999;Kotoulas, 2004). Bu durum Türkçe, İtalyanca ve Yunanca gibi dillerin İngilizce ve Fransızcaya kıyasla basit bir hece yapısı ve geniş olmayan sesli harf repertuvarına sahip olmasına dayandırılmaktadır (Anthony vd., 2011;Durgunoğlu ve Öney, 1999).…”
Section: Sesbilgisel Farkındalıkunclassified
“…해독과 관련된 대표적인 음운처리능력인 음운인식(phonological awareness)은 각 개인이 속한 언어의 말소리를 지각하고 조작하 는 능력으로 해독능력과 밀접한 연관이 있는 요인으로 밝혀졌다 (Kim, Yoo, & Kim, 2010;Scarborough, 1998;Swan & Goswami, 1997;Yoon, 2015). 음운인식능력은 음절인식부터 음절체, 종성, 음 소인식 순서로 발달하며 (Kim et al, 2010), 특히 음소 수준의 인식 이 읽기능력과 관련성이 높다고 알려져 있어 (Pennington & Bishop, 2009) 음운인식은 해독을 습득하는 저학년과 불투명한 철자체계인 영 어에서 좀 더 중요한 음운처리능력으로 나타나 학년이나 철자체계 의 깊이(orthographic depth)가 영향을 미치는 요인으로 나타났다 (Pinto, Bigozzi, Tarchi, Vezzani, & Accorti Gamannossi, 2016;Kotoulas, 2004) (Denckla & Cutting, 1999;Georgiou, Parrila, & Kirby, 2009). 빠른 이름대기능력도 읽기발달과 읽기장 애를 예측하는 음운처리능력 중 하나로 간주한다 (Wolf & Bowers, 2000).…”
unclassified